Performance of Bamboo Husk-Reinforced Cement Board as a Sustainable Alternative to Synthetic Fibers - Mohd Ali Nashruddin, Nurul Aqilah; Mohd Apandi, Najeeha (Progress in Engineering Application and Technology, 2025)
To promote ecologically friendly building methods, this study explores the partial substitution of cement board with bamboo husk, a plentiful and sustainable agricultural waste. Because of its low cost, inherent thermal insulating qualities, and potential to lessen cement's environmental impact, bamboo husk was chosen. Different percentages of bamboo husk treated with NaOH (0%, 2%, 3%, 4%, and 5%) were used to create cement boards, which were then allowed to cure for 28 days. Following ASTM C1185 and ASTM C177 standards, physical attributes such as thickness swelling, water absorption, and thermal conductivity were assessed. The findings indicated that the amount of bamboo husk had an impact on every property that was tested. All samples stayed below the 0.5% threshold, with the 2% husk sample exhibiting the least amount of thickness swelling (0.03%). Higher husk content resulted in a modest increase in water absorption, although it stayed within reasonable bounds. The best thermal insulation was found in the 4% husk sample (0.091 W/m·°C). Higher husk levels, however, occasionally resulted in decreased performance and increased porosity. The best balanced performance was obtained overall with a 2% bamboo husk composition, suggesting that it has the potential to be a sustainable addition for creating lightweight, environmentally friendly, and thermally efficient cement boards for non-structural uses.